2021
DOI: 10.1007/s11356-021-15413-0
|View full text |Cite
|
Sign up to set email alerts
|

Source profiling of air pollution and its association with acute respiratory infections in the Himalayan-bound region of India

Abstract: The studies related to air pollution and its association with human health over the mountainous region are of utmost importance, and are sparse especially over the Himalayan region of India. This study gives an understanding of increase in the occurrence of respiratory diseases due to the accumulation of pollutants during winter season in the Himalayan region (Kashmir valley). The linkages between various atmospheric variables and clinically validated data have been done using various datasets procured from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…22 PM 2.5 can pass through the human body through breathing (inhalation and exhalation) and accumulates in the lungs or trachea, causing severe hazard to human health. A significant number of epidemiological studies have shown that long-term exposure to PM 2.5 can result in respiratory problems, 24 cardiovascular diseases, and lung irritation, hence, the rise in morbidity and mortality. Exposure to PM can cause blood clot, 25 which may eventually lead to heart attack.…”
Section: Introductionmentioning
confidence: 99%
“…22 PM 2.5 can pass through the human body through breathing (inhalation and exhalation) and accumulates in the lungs or trachea, causing severe hazard to human health. A significant number of epidemiological studies have shown that long-term exposure to PM 2.5 can result in respiratory problems, 24 cardiovascular diseases, and lung irritation, hence, the rise in morbidity and mortality. Exposure to PM can cause blood clot, 25 which may eventually lead to heart attack.…”
Section: Introductionmentioning
confidence: 99%
“…The current analysis showed a significant effect of fire events (i.e. forest or agricultural fires) over northern India and the Himalayan foothills during mid-March-April 2021 [7,66], which significantly affect aerosol loading over the region, the formation of atmospheric brown clouds, and haze conditions and significantly attenuated levels of GHI [67][68][69].…”
Section: Fire Countsmentioning
confidence: 72%
“…The shallower boundary layer in January implies that PM 2.5 is concentrated close to the source regions and near the surface. With the increase in boundary layer height in spring, aerosols disperse to higher altitudes and can uplift up to the Himalayan range [66], leading to lower concentrations near the surface. Figure A4 shows the cross-section of PM 2.5 and horizontal wind through Nainital, along a constant latitude of 29.4 • N between 70 • E and 90 • E. The vertical distribution of air pollution was also investigated with the CALIPSO Li-DAR observations, which provide the vertical distribution of total attenuated backscatter (TAB) during the CALIPSO nighttime overpass on 5 April 2021 (Figure 8).…”
Section: Vertical Distribution Of Pm25mentioning
confidence: 99%
“…EC has a cancer potency factor equivalent to carcinogenic compounds such as benzo[a]pyrene, and upon being bio-accumulated in the environment it can affect human health [ 26 ]. EC, compared to other particulates, it has smaller size and can penetrate through the walls of the respiratory organs and enter into the blood stream of the body and reach other organs [ 8 , 21 , 22 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Moreover, EC can disturb the autonomic nervous system and, subsequently, increase the susceptibility of the heart to fatal dysrhythmias [ 3 , 9 , 10 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%